1991
DOI: 10.1111/j.2042-3306.1991.tb03715.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of subclinical tendon injury from ground reaction force analysis

Abstract: In this study a method of analysing ground reaction forces was developed to help in the diagnosis of subclinical flexor tendon injury. A Kistler force plate was used to obtain records from a population of Thoroughbreds in National Hunt training over a period of two years. Characteristic features of the force patterns generated were measured and shown to have low variance, both between horses and over a period of two racing seasons in animals that were sound throughout the trial. Specific changes in the loading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 16 publications
(10 reference statements)
2
35
1
Order By: Relevance
“…Horizontal acceleration peaks of the hooves have been studied earlier by Back et al 25,27 They found that the horizontal hoof-acceleration peak comes immediately after the vertical hoof-acceleration peak, which is in accordance with the results of our experiment. Only a few data on the maximum horizontal acceleration amplitude during impact are currently available in the literature, and measurements were done under different circumstances.…”
Section: Discussionsupporting
confidence: 94%
“…Horizontal acceleration peaks of the hooves have been studied earlier by Back et al 25,27 They found that the horizontal hoof-acceleration peak comes immediately after the vertical hoof-acceleration peak, which is in accordance with the results of our experiment. Only a few data on the maximum horizontal acceleration amplitude during impact are currently available in the literature, and measurements were done under different circumstances.…”
Section: Discussionsupporting
confidence: 94%
“…* 'dimple' in the vertical ground reaction force curve in the early stance phase ( Barr et al, 1995). Although the mean BW of the five ponies in the present study (279 kg) was higher than that of the 48 ponies (189 kg) in the study of Barr et al (1995), the slightly higher forelimb PVF in ponies at trot compared to other breeds such as Dutch Warmbloods (118% BW) (Merkens et al, 1993), Standardbreds (113% BW) (Seeherman et al, 1987), Thoroughbreds (108% BW) (Dow et al, 1991) and Quarter Horses (101% BW) was confirmed.…”
Section: Repeatability Of Measurementscontrasting
confidence: 49%
“…Peak loads range from two thirds of the horse's body weight at the walk, to the equivalent of its body weight at the trot, up to twice its body weight at the jump reception. The kinetics of lameness have been studied using equine patients that have clearly diagnosed lamenesses (navicular disease [43][44][45][46][47][48] and tendonitis of the superficial digital flexor tendon [44,49]) or applying different lameness models (endotoxin-induced synovitis model [50], surgically created chip fracture osteoarthritis model [51,52], collagenase-induced tendonitis model [53][54][55][56], and sole pressure model [30,[57][58][59]). The increasing number of clinical studies involving GRF measurements published in the past 5 years reflects the growing interest in quantitative lameness assessment to reliably test effects of drugs [60][61][62] and other therapeutic interventions [63,64] of surgical procedures, or therapeutic shoeing [65][66][67].…”
Section: Methodologic Aspectsmentioning
confidence: 99%